Real-Time Monitoring for a Building-Integrated Photovoltaic System based on the Internet of Things and a Web Application - Ftirich, Atef; Bouaziz, Bechir; Bacha, Faouzi (Engineering, Technology & Applied Science Research, 2024)
Building-Integrated Photovoltaic (BIPV) systems have become the most attractive clean solution for generating sustainable energy in building structures. Thus, the challenge of improving their efficiency is of extreme importance. The deployment of remote monitoring systems based on the Internet of Things (IoT) presents an opportunity to reduce the overall costs associated with BIPV systems. However, the performance of these monitoring systems varies depending on different parameters and environmental conditions. This paper presents a low-cost IoT-based prototype for monitoring of a solar photovoltaic panel connected to a battery. The current, voltage, and temperature values of the panel and battery, along with environmental parameters such as humidity, temperature, and solar irradiance were measured using low-cost relevant sensors. The data were sent and stored in PostgreSQL database servers through the Raspberry Pi4 Wi-Fi microcontroller board. Real-time visualization of data was facilitated through Web monitoring interfaces. The intelligent monitoring system was implemented in a facility located in Gabes, Tunisia.